THE EFFECT OF SHARIA FINANCIAL LITERACY AND INCLUSION ON THE PERFORMANCE OF THE JAKARTA ISLAMIC INDEX - Musthofa, Khabib; Alfath, Muhammad Sandy; Nafidzi, Elman (Jurnal Syarikah : Jurnal Ekonomi Islam, 2025)
This study aims to analyze the effect of literacy and sharia financial inclusion on the performance of the Jakarta Islamic Index (JII) in 2016, 2019, 2022, and 2024. The research approach used is quantitative with secondary time series data obtained from the Indonesia Stock Exchange (IDX) and the Financial Services Authority (OJK). The analysis was conducted through classical assumption tests and multiple linear regression using SPSS 27. The results of the study indicate that neither Islamic financial literacy nor inclusion, either partially or simultaneously, has a significant effect on JII performance, with significance values above 0.05. The negative regression coefficients for both variables indicate that increases in literacy or inclusion do not necessarily drive an increase in JII performance. This is likely due to the dominance of institutional investors in JII transactions and the growth of inclusion being more focused on the banking, insurance, and microfinance sectors compared to the Islamic capital market. The insignificant F-test and t-test results suggest that other factors, such as macroeconomic conditions and issuer performance, have a more dominant influence on JII movements. These findings underscore the need for policies that link Islamic financial literacy and access to participation in the Islamic capital market.